2017
DOI: 10.1016/j.jaad.2016.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adults with facial port-wine stains

Abstract: Background Facial port-wine stains (PWS) are considered by some an aesthetic skin problem, yet impact on quality of life (QoL) has not been objectively documented. Objective We sought to (1) characterize the effect of PWS on QoL in adults, (2) to identify the clinical and demographic factors that affect QoL, and (3) to compare our results with QoL studies in other skin conditions. Methods In total, 244 adults with facial PWS completed an online QoL survey, which included the Skindex-29 instrument. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 34 publications
3
83
1
3
Order By: Relevance
“…Facial PWS is a debilitating condition that has significant functional and psychosocial impact on affected individuals. Although prior studies have demonstrated quality-oflife impairment secondary to facial PWS, [35][36][37] this is the first study to objectively quantify the utility of hypertrophic and laser-treated facial PWS health states among a convenience sample of community volunteers. One previous study investigated TTO and willingness to pay for laser therapy among patients who had already undergone treatment for facial PWS, but was limited by a small sample size and preclusion of VAS and SG methods.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Facial PWS is a debilitating condition that has significant functional and psychosocial impact on affected individuals. Although prior studies have demonstrated quality-oflife impairment secondary to facial PWS, [35][36][37] this is the first study to objectively quantify the utility of hypertrophic and laser-treated facial PWS health states among a convenience sample of community volunteers. One previous study investigated TTO and willingness to pay for laser therapy among patients who had already undergone treatment for facial PWS, but was limited by a small sample size and preclusion of VAS and SG methods.…”
Section: Discussionmentioning
confidence: 98%
“…Herein, societal-derived utility of these health states was measured objectively using standardized and well-established methods (VAS, SG, and TTO) 39,40 among naïve observers. Several studies have shown that patients' quality of life, psychosocial adjustment, and self-esteem are negatively impacted by a facial PWS, [35][36][37]41 with emotional distress correlating with size and darkness of the PWS, resulting from progressive dilation of the ectatic vasculature. Our study has demonstrated that a sample of naïve observers equates the burden of living with hypertrophic facial PWS (0.71 -0.24, 0.83 -0.23, 0.83 -0.21) to that of monocular blindness (0.73 -0.21, 0.86 -0.21, 0.87 -0.18), a recognized functional impairment associated with known utility decrements.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that adults with port-wine stain (PWS) have a self-reported significantly reduced quality of life, with 33.6% reporting anxiety or depression. 2 This research reiterates the importance of including all eligible children into the laser treatment pathway. Any Fitzpatrick skin type can successfully undergo laser treatment, but increased caution is needed in darker skin types, owing to the increased risk of thermal injury.…”
Section: Conditions Treated With Lasermentioning
confidence: 88%
“…Conditions suitable for laser treatment include facial lesions that cause disfigurement, vascular lesions that bleed superficially and conditions that affect the child’s confidence. A recent study demonstrated that adults with port‐wine stain (PWS) have a self‐reported significantly reduced quality of life, with 33.6% reporting anxiety or depression . This research reiterates the importance of including all eligible children into the laser treatment pathway.…”
Section: Conditions Treated With Lasermentioning
confidence: 92%
“…This pathology can be classified as either nonsegmental, due to the symmetrical arrangement of the lesions, or segmental, due to the nonsymmetrical disposition of the lesions [ 4 ]. Vitiligo is not a fatal pathology; however, the patient’s quality of life is drastically diminished due to social reasons such as discrimination, social isolation, and depression [ 5 , 6 , 7 , 8 , 9 ]. Current treatments for vitiligo are focused on the promotion of repigmentation through the stimulation of melanogenesis and decreased immune system activity and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%